The hours for the prince - Bizelli, José Luís (Universidade Estadual Paulista / UNESP, 2009)
This paper tries to understand the structure of the machiavelic thought through the tension that exists among some of this fundamental of political activity. In the case, the "will" of transformation of the authors who want the power and the historical determinations.